The Pejuang Subuh Program as a Model of Qur’anic Literacy and Religious Formation for Children in Mosque-Based Settings - Fikri, Khairul; Amril, Dapit (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The Pejuang Subuh (Dawn Warriors) Program is a community service initiative aimed at strengthening Qur’anic literacy among children and adolescents through regular post-dawn prayer activities at Baitul Makmur Minangkabau Mosque, West Sumatra. This program was developed in response to the declining interest of the younger generation in the Qur’an and their diminishing engagement in mosque activities. The implementation employed a community-based, participatory-educational approach, comprising preparation, daily activities, and periodic evaluation. Participants included children aged 7–15 years, guided by mosque youth serving as facilitators. Core activities encompassed tilāwah (Qur’anic recitation), taḥsīn (recitation improvement), the transmission of Qur’anic moral values, and reflective discussions. The program yielded significant improvements in Qur’anic reading skills, worship discipline, and the development of participants' Islamic character. Moreover, it fostered an inclusive and vibrant mosque atmosphere and enhanced intergenerational participation within the local community. Challenges such as inconsistent attendance, limited facilitators, and varied participant abilities were addressed through adaptive and collaborative strategies. This program has proven to be a best practice model that can be replicated in other mosques with appropriate contextual adjustments. In conclusion, Pejuang Subuh is an effective model for nurturing Qur’anic literacy and religious character through simple yet sustainable community-based activities.